A case study of the Iranian national railway and its absolute capacity expansion using analytical models. Issue 4 (2nd October 2017) - Bevrani, Bayan; Burdett, Robert L.; Yarlagadda, Prasad K. D. V.
Abstract: Identifying railway capacity is an important task that can identify 'in principal' whether the network can handle an intended traffic flow, and whether there is any free capacity left for additional train services. Capacity determination techniques can also be used to identify how best to improve an existing network, and at least cost. In this article, an optimization approach has been applied to a case study of the Iran national railway, in order to identify its current capacity and to optimally expand it given a variety of technical conditions. This railway is very important in Iran and will be upgraded extensively in the coming years. Hence, the conclusions in this article may help in that endeavor. A sensitivity analysis is recommended to evaluate a wider range of possible scenarios. Hence, more useful lower and upper bounds can be provided for the performance of the system.